Life at the margins: The social, economic and ecological importance of mangroves - Acharya, Gayatri (Instituto de Ecología, A.C., 2016)
Coastal communities are dependent on the resources available in mangrove ecosystems. Despite their usefulness because of the vital ecological services they provide, mangroves are under heavy stress. The loss of these ecosystems would mean local, national and global welfare losses. Quantifying those losses accurately and using them to make more informed decisions about land use and land conversion, is a challenging task. Economic values associated with healthy mangrove ecosystems can be generated through economic analyses that attempt to measure the use and non-use values of these ecosystems. The values associated with mangroves are positive and have been used to influence policy. An optimal mangrove management strategy should recognize that the products and ecosystem services provided by mangroves can be very significant to human welfare. The creation of markets for forest environmental services allows the values of multiple-use ecosystems such as mangroves to be recognized and utilized in decision making. Taking an ecosystem approach to the management of these resources can help to understand the complexity of ecological and socio-economic processes within mangrove ecosystems. In developing countries, such analyses are essential for promoting equity and poverty alleviation. The value of mangrove ecosystems can best be realized when decision makers make the effort to accurately weigh the costs and benefits of conservation versus conversion. Projects and programs that are judged to be commercially viable must also be socially profitable.